If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + -10y = -48 Combine like terms: -6y + -10y = -16y -16y = -48 Solving -16y = -48 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-16'. y = 3 Simplifying y = 3
| 6x+4=-8+4x | | 533=q^2+13q+23 | | 4-x-5x=58 | | -15+36=-10 | | 25=-5+5y | | -2x^2-4x=6 | | 9x+640x-5700=0 | | 6+4x=-2x+78 | | 7y=32-4y | | 1313=q^2+2213-60q | | -3x(x+5)=-3x+5 | | 3/4+2/5= | | 2x+32=32 | | 3x-8-7x=32 | | 10cos^2(30)= | | (x+9)(3x+2)=0 | | x+72=2x+60 | | 1+2x=3x-5 | | x^2-5=2x-1 | | (6x^2y^3+x^2-3x^3y^2)-(2x^3y^2-4y^3+7x^2)= | | 9x^3+27x^2-2x-6=0 | | 3x-9=5x+13 | | 7x+3y+8z-4x-4z-5y= | | 3e+9=27 | | 5x+11=-2-14x | | 3x+11=-14-2x | | (3w^2+3w)-(-8w^2-3w+8)= | | 3e-9=27 | | -3x+5=3x-5 | | 5x+2=8x+6 | | (2x+4)+1=5x-9 | | 5*3(y-4)=5(y+2)-y |